Educação histórica e o uso das TDICs: uma proposta de ensino de história utilizando as mídias digitais - Bueno, Fernanda Magalhães (2023)
The present research presented to the Course of the Strict Sensu Professional Master's Course of the Graduate Program in Teaching in Basic Education of the Center for Teaching and Research Applied to Education (CEPAE) of the Federal University of Goiás (UFG) has as its object of investigation the possibility of using Digital Information and Communication Technologies (TDICs) in the teaching of History from the theoretical and methodological assumptions of Historical Education. Historical Education is a line of research within the area of teaching History that aims at a didactic built by historians, uniting the assumptions of reference science with classroom practice to understand the development of historical thinking and historical awareness to from the elucidation not only of what is learned in history, but also of how history is learned. Based on the investigation, an educational product entitled “Why Study History? Sequence of three tutorial videos on studying History in basic education” was developed. The product is a sequence of three videos available on the YouTube platform that aims to highlight the significance of the study of the discipline of History in the current school and, finally, to show resources that favor students in the production and sharing of their school work related to the discipline of History, so that they use technology in the service of contact with varied historical sources, in the service of authorship of knowledge and in the service of communication and sharing of their learning. The research methodology consists of bibliographical research, application of questionnaires with the objective of investigating the conception of students of the ninth year of elementary school of a private school in Goiânia about what History is, its usefulness and, also, to investigate the relationship of these students with the TDICs. From the analysis of the students' answers to the questionnaires and based on the theory and methodology of Historical Education, the educational product was developed with the objective of filling the lack of guidance in relation to the discipline of History and the use of TDICs. The educational product was presented to the students and evaluated by them in order to analyze its relevance to the educational scenario.